ANALISIS SEGMENTING DAN TARGETING TEMPAT BILLIARD DI WILAYAH JAKARTA BARAT - Putri Maulidina; Nurhassanah Sofjan (EBID: Ekonomi Bisnis Digital, 2023)
One of the objectives of providing billiard game entertainment services is to complement the market demand for billiard lovers in the scope of Jakarta, especially in the Greenlake city area, especially due to the lack of places to play billiards in the West Jakarta area that provide property and a comfortable and exciting place. In general, the craze of the Indonesian people, especially in Jakarta, for Billiard games is increasing, as seen by the number of new Billiard businesses or places to play in Jakarta. Billiard playing places that are in demand are certainly different, because the atmosphere of the Billiard playing place itself is a characteristic of each Billiard service provider. Likewise, the competitors of billiard game service providers in Jakarta are the most popular places to play in each region. Segmentation and targeting must be detailed in order to achieve customer satisfaction. The method used is descriptive qualitative using a purposive sampling approach